1990
DOI: 10.2307/3282988
|View full text |Cite
|
Sign up to set email alerts
|

Axenic Culture and Characterization of Giardia ardeae from the Great Blue Heron (Ardea herodias)

Abstract: Trophozoites of Giardia ardeae were obtained from the great blue heron (Ardea herodias) and established in axenic culture using the TYI-S-33 medium. The generation time in culture for G. ardeae was 22-25 hr, which was 3-fold longer than for Giardia duodenalis (WB strain). A morphological comparison of trophozoites in the original intestinal isolate to those grown in culture revealed that they were identical for the following characteristics: a pyriform-shaped body, a ventral adhesive disc with a deep notch in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
0
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 20 publications
1
29
0
4
Order By: Relevance
“…found in the white stork, closely resembled G. ardeae observed in herons. The apparently single caudal flagellum, the deeply notched adhesive disk, the shape and position of the median body, and the nuclei were in accordance with those reported for G. ardeae of gray heron and great blue heron (Georgi et al, 1986;Erlandsen et al, 1990;Forshaw et al, 1992). The morphological characteristics of the trophozoites found in our white stork chick support the classification of these parasites within the G. ardeae group.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…found in the white stork, closely resembled G. ardeae observed in herons. The apparently single caudal flagellum, the deeply notched adhesive disk, the shape and position of the median body, and the nuclei were in accordance with those reported for G. ardeae of gray heron and great blue heron (Georgi et al, 1986;Erlandsen et al, 1990;Forshaw et al, 1992). The morphological characteristics of the trophozoites found in our white stork chick support the classification of these parasites within the G. ardeae group.…”
supporting
confidence: 74%
“…possessing a single caudal flagellum, which was found in a gray heron (Ardea cinerea) and was named G. ardea (Kulda and Nohý nková, 1995). More recently, G. ardeae was isolated from the great blue heron (A. herodias) and characterized genetically (Erlandsen et al, 1990). Phenotypically identical Giardia spp.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5,7 In the wild, a wide variety of aquatic and semiaquatic mammals and birds 8 can be a source of waterborne Giardia cysts. 5,9,10 Studies on giardiasis in a variety of birds suggest they may be zoonotic reservoirs; 7,[9][10][11][12] however, these indications have not been proven. 13 As reviewed by Hopkins and others, 14 numerous studies demonstrated genetic and antigenic similarities among Giardia cyst isolates from humans and other mammalian hosts.…”
mentioning
confidence: 99%